Capture the flag challenge: design and implementation - Oong, Jie Xiang (Nanyang Technological University, 2023)
To provide students of NTU’s CZ4067 (Software Security) module the opportunity to practise their software exploitation skills, a Capture The Flag (CTF) competition has been included in the module assessment. As in any software development practice, the development of a CTF challenge bank catering to CZ4067 students comprises common tools and design considerations and requires continuous integration. This project focuses on the creation of interesting and relevant challenges tailored for CZ4067 students and proposes a standard for managing challenges in a central repository. A subset of new challenges was released to CZ4067 students in AY22/23 Semester 2, and the results published in this report highlighted the importance of each CTF development phase from ideation to testing.